The e-commerce supply chain and environmental sustainability: An empirical investigation on the online retail sector - Prakash Rao (Taylor & Francis Group, 2021)
Despite the significant growth of e-commerce in recent years, especially in the business-to-consumer (B2C) online retail sector, its positive and negative environmental implications are unclear from previous research. To understand the environmental impacts of e-commerce, two conceptual models were first developed from the literature. Next, using 303 responses collected through a structured questionnaire from the GCC countries, the proposed models, including the relevance/appropriateness of each construct and its underlying items, were validated, and then the hypothesized relationships between them were assessed. The findings of Model 1 showed that green consumerism does shape the consumers’ positive and negative environmental attitudes towards e-commerce, which in turn was found to influence the behavioral intention to use e-commerce channels. In Model 2, positive environmental attitudes no longer predicted behavioral intention with the introduction of perceived ease of use and perceived usefulness constructs as consumers preferred ease of use and usefulness of e-commerce over positive environmental factors. Interestingly, the impact of negative environmental attitudes on behavioral intention remained even in the presence of perceived ease of use and perceived usefulness. The study provides critical insights for practitioners and policymakers in promoting and leveraging the positive environmental benefits of e-commerce, while at the same time strive to minimize/eliminate its negative environmental impacts. The study is arguably the first empirical attempt in understanding the positive and negative environmental implications of e-commerce and its impact on the consumer intention to use e-commerce, and hence the study findings are novel.